Analysis of the modern interaction of the labor market and the professional education in Kazakhstan - Borbаsovа Z.N.; Sedlarski Т.; Bezler, O.D. (BUKETOV BUSINESS REVIEW, 2019)
The efficient interaction of the labor market and higher professional education institutions, the integration of their main purposes and objectives play an important role in providing the economy of the country with the key resource, that is, highly professional specialists. The errors in coordination of these most important market subsystems can result in irreversible economic losses and negative social consequences, as, in the market environment, the economic development and competitiveness of the country is largely determined by high quality human resources. In this connection, the objective of this article is to analyze the interaction of the labor market and the professional education on the basis of the economic and statistical analysis of the dynamics of employment, including employment of young people at the age of 15–28 with regard to their education, vacancies, professional groups, and the dynamics of unemployment and the educational systems indicators. The analysis revealed that when choosing a future profession young people are focused more on the specialty prestige, not on the real needs of the labor market, therefore graduates from educational institutions do not match the demand on the labor market. This article offers directions of improvement of the existing integration mechanisms of the labor market and the educational services market.